Uniaxial compressive strength of first-year and multi-year sea ice - Sinha, N. K. (1984)
Strain-rate and stress-rate sensitivity of the compressive strength of first-year columnar-grained ice, first-year congealed frazil ice, and columnar-grained ice from an old floe have been investigated with load applied in the horizontal plane. In spite of similar salinity and density, the frazil ice proved to be considerably stronger than the columnar-grained ice. The strength of porous old floe ice with columnar-grained structure was very much the same as that of first-year ice of similar structure, but the clear bulk ice of the old floe was strongest. Rate sensitivity of strength for the three types of saline ice was similar to that of fresh-water ice. Ductility of the old clear ice (as measured by the strain at upper yield) was the same as that of fresh-water ice; ductility of porous old ice was comparable to that of new frazil ice. New columnar-grained ice proved to be the most ductile material. Nous avons étudié la sensibilité de la résistance en compression aux taux de déformation et de contrainte de la glace colonnaire de première année, du frasil congelé de première année et de la glace colonnaire d'une vieille banquise. L'étude a été faite sous charge appliquée dans le plan horizontal. En dépit d'une salinité et d'une densité semblables, le frasil s'est montré beaucoup plus résistant que la glace colonnaire. Bien que la résistance de la glace poreuse à structure colonnaire d'une vieille banquise ait été la même que celle de la glace de première année ayant la même structure, la glace claire massive d'une vieille banquise s'est avérée la plus forte. La sensibilité de la résistance en compression aux taux de déformation et de contrainte des trois types de glace saline était semblable à celle de la glace d'eau douce. La ductilité de la vieille glace (déterminée par la déformation à la limite supérieure de la résistance) était la même que celle de la glace d'eau douce; la ductilité de la vieille glace poreuse était comparable à celle du frasil. La nouvelle glace colonnaire s'est avérée le matériau le ...